IMPROVING STUDENTS’ SPEAKING SKILL THROUGH PICTURE SERIES AT THE GRADE X OF ISLAMIC BOARDING SCHOOL OF SABBHISMA PADANG - Lailatul Husna; Dedi, Dedi (Journal of Social and Economics Research, 2024)
This research was classroom action research [CAR] because the research aimed at finding out the practical problem solving. Jhonson (2005) states classroom action research is a process of studying class situation or real class in improving and understanding the quality of action or instruction. the students prefer using Indonesian language in speaking with their friends, teachers, and other people. These cases are caused by some factors; students’ input, limited facilities, unsupported school environment and teacher strategies that used in teaching and learning process in the classroom. the comparison the students’ speaking test between speaking test I and speaking test II. At the speaking test I, the students’ purpose was 6.6 , the score increased to be 8.2 on the speaking test 2. The data of using picture series in teaching and learning recount text showed that it could improve the students’ speaking skill because the picture series were consisted a set of pictures, including sequences of events that create a story.